Clinical, Laboratory Features and Clinical Courses of Patients with Wiskott Aldrich Syndrome and X–linked Thrombocytopenia–A single center study. (4th July 2022) - Bildik, Hacer Neslihan; Cagdas, Deniz; Ozturk Kura, Aysenur; Oskay Halacli, Sevil; Sanal, Ozden; Tezcan, Ilhan
ABSTRACT: Objective: Wiskott Aldrich Syndrome is an X-linked primary immunodeficiency disorder characterized by microthrombocytopenia, severe immunodeficiency, and eczema. To define clinical-laboratory features, genetic defects (known/novel) of 23 patients of Wiskott Aldrich Syndrome/X-linked Thrombocytopenia (WAS/XLT) cohort, establish relationships between molecular defects and clinical features if present, evaluate patients who underwent hematopoietic stem cell transplantation (HSCT) and did not. Methods: Qualitative analysis from patients' hospital files and Sanger sequencing for molecular diagnosis was performed. Twenty-two WAS patients and one XLT patient were included in the study. Results: The median age of diagnosis was 15 months (2.5–172 months). The most common symptom was otitis media and all patients had microthrombocytopenia. Autoimmune findings were detected in 34.7% (8 patients) of the patients; three patients (13%) had positive anti-nuclear antibody (ANA), three patients (13%) hemolytic anemia, one patient autoimmune neutropenia, two patients vasculitis, and one patient demyelinating polyneuropathy. Nine of the 23 (39, 1%) patients had HSCT with nearly 90% success. We identified 13 different mutations in our cohort; seven were novel. Conclusions: HSCT is the only curative treatment for WAS. The study confirms that early diagnosis is very important for the success of therapy, so we must increase awareness in society and physicians to keep an eye out for clues. Our study cohort and follow-up period are not sufficient to establish phenotype-genotype correlation, so a larger cohort from various centers with longer follow-up will be more decisive.